Analisis Kualitas Pelayanan Perpustakaan Kerano Kuncoro Di Desa Sri Kuncoro Kecamatan Pondok Kelapa Kabupaten Bengkulu Tengah - Titi Darmi; Intan Dwi Safitri Dwi Safitri; Rekho Adriadi (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2022)
Education is one thing that is very important and is a necessity for all people to achieve prosperity. The government continues to make improvements by changing policies in education sector, such as the policy of Merdeka Belajar, which means to be free to innovate, learn independently, and be creative. In line with the concept of Merdeka Belajar, the existence of libraries as one of the non-formal education units or public service institutions has a very important role in producing human resources with superior character, intelligence, and competitive. One of the such institutions is the Kerano Kuncoro library. This study aims to describe service quality of the Kerano Kuncoro library in Sri Kuncoro Village, Pondok Kelapa District, Bengkulu Tengah Regency and the efforts made by the Kerano Kuncoro library in improving service quality. This study uses a descriptive method with a qualitative approach. Data collection technique used were observation, interviews, and documentation. The results of this study indicate that the quality of service in Kerano Kuncoro village library is good based on three-dimensional service quality measurements, namely the quality of interaction, the quality of the physical environment, and the quality of results along with their indicators. Even so, there are still some indicators that have not gone as expected, like the limited number of experts in library sector. However, to produce excellent service, the Kerano Kuncoro library makes several efforts such as conducting library promotion activities, developing and enhancing librarian creativity and developing library material collections. This is evidenced by the various awards won by the library at both the district and provincial levels